The Mediating Role of Work Motivation in the Relationship between Transformational Leadership, Organizational Culture, and Organizational Communication on Employee Job Satisfaction at CV Raffana Kids Store - Abdul Tahir; Iwan Asmadi; Musakirawati; Fitri Rezeki (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2026)
Objective: This study aims to examine the influence of transformational leadership, organizational culture, and organizational communication on employee job satisfaction and to analyze the mediating role of work motivation at Cv Raffana Kids Store, which experienced increased absenteeism and employee turnover throughout 2023. A quantitative descriptive design was employed using a saturated sampling technique involving 76 employees. Data were collected through questionnaires and analyzed using Partial Least Squares with SmartPLS by evaluating the outer model, inner model, and path coefficients. The findings reveal that organizational communication has a positive and significant effect on job satisfaction, while organizational culture and transformational leadership do not show a significant direct effect. Work motivation is also not proven to mediate the relationships between the organizational variables and job satisfaction. The R Square values indicate a strong model capability in explaining the variance of job satisfaction and work motivation. The novelty of this study lies in highlighting the dominant role of organizational communication in improving job satisfaction within a small-scale retail context.